Radial Nerve Mobilization Decreases Pain Sensitivity and Improves Motor Performance in Patients With Thumb Carpometacarpal Osteoarthritis: A Randomized Controlled Trial - Villafañe, Jorge H.; Silva, Guillermo B.; Bishop, Mark D.; Fernandez-Carnero, Josue (Archives of physical medicine and rehabilitation, 2012)
Villafañe JH, Silva GB, Bishop MD, Fernandez-Carnero J. Radial nerve mobilization decreases pain sensitivity and improves motor performance in patients with thumb carpometacarpal osteoarthritis: a randomized controlled trial. To examine the effects of radial nerve mobilization on pain sensitivity and motor performance in subjects with secondary thumb carpometacarpal osteoarthritis. Randomized controlled trial. Treatment and placebo were given for 4 weeks. Measurements were taken before intervention, after 1 month (first follow-up), and after 2 months (second follow-up). Patients from the Department of Physical Therapy, Azienda Sanitaria Locale 3, Collegno (Italy). Participants (N=60; age range, 70–90y) with right-dominant hand secondary thumb carpometacarpal osteoarthritis without other motor-related pathology. All patients completed the study. No patients were withdrawn from the study. Sliding mobilization of the proximal-distal radial nerve or intermittent ultrasound therapy, used as placebo. We hypothesized that radial nerve mobilization induces hypoalgesia and increases strength in secondary thumb carpometacarpal osteoarthritis. We measured pressure pain threshold (PPT) at the trapeziometacarpal joint, the tubercle of the scaphoid bone, and the unciform apophysis of the hamate bone by algometry. Tip pinch strength and tripod pinch strength were measured by a mechanical pinch gauge. Treatment increased PPT by 3.33±.24kg/cm2 (P<.001) in the trapeziometacarpal joint and was maintained until first follow-up and second follow-up. Also, PPT in the scaphoid bone and hamate bone was increased (P<.001 and P<.02, respectively). Variables in the placebo group remained unchanged. Tip pinch strength increased by 2.22±.22kg (P<.04) and tripod pinch strength by 2.83±.24kg (P<.019). Radial nerve mobilization decreases pain sensitivity in the trapeziometacarpal joint and increases tip pinch strength.